PENERAPAN PEMBELAJARAN DEEP LEARNING BERBASIS ALAT MUSIK TRADISIONAL TERHADAP PEMAHAMAN KONSEP SISWA KELAS VIII SMPS YKPP SUNGAI PAKNING PADA MATERI GETARAN DAN GELOMBANG - Satira, Salma; Irawan, Dedi; Irianti, Mitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The results of the PISA international assessment show that Indonesian students' scientific literacy skills are still below the average of OECD countries. This condition indicates that students' conceptual understanding abilities have not developed optimally. In science learning, especially vibration and wave material, students tend to memorize material without understanding the meaning of the concepts being learned. One alternative that can be applied to overcome this problem is traditional musical instrument-based deep learning. This study aims to describe the conceptual understanding of eighth-grade students of SMPS YKPP Sungai Pakning on vibration and wave material through the application of traditional musical instrument-based deep learning and to determine the differences in conceptual understanding of students who learn using traditional musical instrument-based deep learning and students who learn using conventional learning. This study uses a quantitative approach with a quasi-experimental type and a posttest-only control group design. The research sample consisted of 44 students divided into an experimental class and a control class. Data collection was carried out through a 20-question conceptual understanding test. Data were analyzed using descriptive and inferential statistical tests through normality and homogeneity tests, as well as the Independent Sample t-Test. The results showed that the average score of the experimental class was higher. The significance value was 0.022, indicating a significant difference between the two groups. The results of the study indicate that traditional musical instrument-based deep learning is effective in improving students' conceptual understanding of vibrations and waves